Non-surgical management of severe alveolar fissure through orthodontic treatment in an adult patient. Case report - Leiva, Noemí (2018)
The labial-alveolar-palatal cleft is the most common congenital malformation among craniofacial anomalies. Due to its multiple alterations, it directly impacts the quality of life of patients. Its management is interdisciplinary and the treatment must start from birth. The aim of this case report is to show the integral orthodontic management of an adult patient with an untreated unilateral alveolar cleft of 18 mm wide, who came to the Dental office pursuing an aesthetic and functional solution without undergoing surgery. Through a fixed orthodontic multibrackets treatment it was possible to contact the alveolar ridges of the bone defect, obtaining positive results in relation to esthetics and function.